Splicing factors control C. elegans behavioural learning in a single neuron by producing DAF-2c receptor - Masahiro Tomioka (Nature Portfolio, 2016)
Little is known about the molecular mechanisms regulating neuron-specific alternative splicing. Here, the authors identify a combination of RNA-binding proteins regulating neuron-specific expression of the C. elegansinsulin receptor isoform DAF-2c and find disrupting these factors leads to learning deficits.